2018
DOI: 10.1097/acm.0000000000002282
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and Structural Facilitators and Barriers to Becoming a Surgeon: A Qualitative Study of African American and Latino Surgeons

Abstract: The path to a surgical career as experienced by African American and Latino surgeons is heavily influenced by mentors mediating their integration into surgical culture and engendering a feeling of belonging. Future surgeons from groups underrepresented in medicine would benefit from identifying aspirational figures early, a structured introduction into the rigors of the profession, and a deconstruction of negative surgical norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…Our findings are in keeping with current literature that demonstrates that DBSH and microaggressions in the workplace not only harm the victim but also undermine the team culture and reduce both the quality of care and patient safety 9 . Results from a United States national survey found that 31.9% reported discrimination based on gender and 16.6% reported racial discrimination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are in keeping with current literature that demonstrates that DBSH and microaggressions in the workplace not only harm the victim but also undermine the team culture and reduce both the quality of care and patient safety 9 . Results from a United States national survey found that 31.9% reported discrimination based on gender and 16.6% reported racial discrimination.…”
Section: Discussionsupporting
confidence: 90%
“…URM doctors are more likely to serve uninsured patients and practice in regional and remote areas, leading to improved patient satisfaction and broader access to care for minorities. Additionally, patients have been shown to be more satisfied with their treatment and doctor‐patient communication when they are managed by a doctor from their own culture 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggests that some of the facilitators to becoming a URM surgeon, such as mentorship and family, are similar to those in our findings. 20 In addition to the novelty that our study offers, it also brings to the forefront voices of URM pediatricians and can inform future works.…”
Section: Discussionmentioning
confidence: 86%
“…‘Most participants highlighted surgical culture, explicitly describing what it means to be a surgeon and how some think surgeons fit a particular mold . One Latino participant commented: “Surgery is kind of clubby …”’ (p.1331) 21 …”
Section: Resultsmentioning
confidence: 99%